Characterization and complexity of transcriptome in Gymnocypris przewalskii using single-molecule long-read sequencing and RNA-seq. (14th May 2021) - Li, Xindan; Wu, Jinming; Xiao, Xinping; Rong, Yifeng; Yang, Haile; Li, Junyi; Zhou, Qiong; Zhou, Weiguo; Shi, Jianquan; Qi, Hongfang; Du, Hao
Abstract: The Tibetan Schizothoracinae fish Gymnocypris przewalskii has the ability to adapt to the extreme plateau environment, making it an ideal biological material for evolutionary biology research. However, the lack of well-annotated reference genomes has limited the study of the molecular genetics of G. przewalskii . To characterize its transcriptome features, we first used long-read sequencing technology in combination with RNA-seq for transcriptomic analysis. A total of 159, 053 full-length (FL) transcripts were captured by Iso-Seq, having a mean length of 3, 445 bp with N50 value of 4, 348. Of all FL transcripts, 145, 169 were well-annotated in the public database and 134, 537 contained complete open reading frames. There were 4, 149 pairs of alternative splicing events, of which three randomly selected were defined by RT–PCR and sequencing, and 13, 293 long non-coding RNAs detected, based on all-vs.-all BLAST. A total of 118, 185 perfect simple sequence repeats were identified from FL transcripts. The FL transcriptome might provide basis for further research of G. przewalskii .